1995
DOI: 10.1063/1.113738
|View full text |Cite|
|
Sign up to set email alerts
|

Picosecond carrier lifetime in GaAs implanted with high doses of As ions: An alternative material to low-temperature GaAs for optoelectronic applications

Abstract: Nonstoichiometric GaAs obtained by implantation with 2 MeV arsenic ions at 1015 cm−2 dose is studied. As-implanted samples show a <200 fs lifetime of photocarriers and low resistivity due to hopping, with mobility less than 1 cm2/V s. Annealing of the samples at 600 °C leads to substantial recovery of postimplant damage, as seen from Rutherford backscattering channeling spectra and mobility increase to about 2000 cm2/V s, but photocarrier lifetime is still about 1 ps. These parameters are similar to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…The structural and electrical characteristics of LT-GaAs and GaAs : As have been shown to be quite similar [8], [9]. The ultrafast optical characteristics of the as-implanted arsenic-rich GaAs materials have been reported [10]- [12]. Subpicosecond carrier lifetimes were observed.…”
Section: Materials and Ultrafast Optoelectronic Properties Ofmentioning
confidence: 78%
See 1 more Smart Citation
“…The structural and electrical characteristics of LT-GaAs and GaAs : As have been shown to be quite similar [8], [9]. The ultrafast optical characteristics of the as-implanted arsenic-rich GaAs materials have been reported [10]- [12]. Subpicosecond carrier lifetimes were observed.…”
Section: Materials and Ultrafast Optoelectronic Properties Ofmentioning
confidence: 78%
“…However, as-implanted or as-grown nonstoichiometric GaAs obtained by using either the arsenic-ion-implantation or the LTMBE process suffer from the following: the crystallinity of the material is degraded [13], [14]. As a result, the carrier mobility is substantially lower [12], [15]. This also leads to a defect-dominated hopping conducting mechanism, which destroys the highly resistive nature of the original substrate [8], [15].…”
Section: Materials and Ultrafast Optoelectronic Properties Ofmentioning
confidence: 97%
“…It has been demonstrated later that the carrier recombination characteristics of the As-ion implanted GaAs closely remind those of LTG GaAs. E.g., electron trapping time in GaAs implanted by 2 MeV energy ions was equal to 30 fs before annealing [70] and 1 ps after annealing at the temperature of 600 o C [81]. Spatially resolved carrier lifetime measurements of the As-ion implanted and annealed GaAs [87] have shown that carriers decay faster at the surface, whereas the precipitates are predominantly nucleating deeper in the bulk of the crystal, in the proximity of the ion-stop range.…”
Section: Ion-implanted Gaasmentioning
confidence: 99%
“…Therefore, the presence of excess arsenic, which could be the source of the As Ga related point defects, can be expected at the surface of all samples irradiated with heavy, high-energy ions. Such defects have been detected by electron-paramagnetic-resonance measurements in As-implanted samples [81] and in some of the Ga + -implanted samples [82].…”
Section: Ion-implanted Gaasmentioning
confidence: 99%
See 1 more Smart Citation